2014
DOI: 10.1021/ie500156d
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Oxidation of Biomass Derived 5-Hydroxymethylfurfural into 2,5-Diformylfuran Catalyzed by Magnetic Separation of Ruthenium Catalyst

Abstract: In this study, aerobic oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-diformylfuran (DFF) was studied over a magnetic catalyst [Fe 3 O 4 @SiO 2 -NH 2 -Ru(III)]. Various reaction parameters were optimized for the oxidation of HMF into DFF. A high DFF of 86.4% and HMF conversion of 99.3% were obtained after 4 h at 120 °C. More importantly, the catalyst also showed high catalytic activity in air, and high HMF conversion of 99.7% and DFF yield of 86.8% were obtained after 16 h. The high catalytic performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 41 publications
0
55
0
Order By: Relevance
“…56 For Ru-PVP/CNT, there is an overlap between Ru 3d and C 1s peak at around 282.5 eV. 18,56 The presence of chlorine peak indicated that Cl − ion acts as the counter ion of Ru 3+ ion. 45 The binding energy at 461.8 and 484.2 eV are assigned to Ru 3p3/2 and Ru 3p1/2, respectively, which demonstrates that the oxidation state of the ruthenium species is Ru 3+ (Figure 8b).…”
Section: Pvp/cnt and Ru-pvp/cntmentioning
confidence: 99%
See 2 more Smart Citations
“…56 For Ru-PVP/CNT, there is an overlap between Ru 3d and C 1s peak at around 282.5 eV. 18,56 The presence of chlorine peak indicated that Cl − ion acts as the counter ion of Ru 3+ ion. 45 The binding energy at 461.8 and 484.2 eV are assigned to Ru 3p3/2 and Ru 3p1/2, respectively, which demonstrates that the oxidation state of the ruthenium species is Ru 3+ (Figure 8b).…”
Section: Pvp/cnt and Ru-pvp/cntmentioning
confidence: 99%
“…45 The binding energy at 461.8 and 484.2 eV are assigned to Ru 3p3/2 and Ru 3p1/2, respectively, which demonstrates that the oxidation state of the ruthenium species is Ru 3+ (Figure 8b). 18,57 The N 1s binding energies are 397.0 and 397.4 eV for PVP/CNT and Ru-PVP/CNT, respectively ( Figure 8c). The observed shift in N 1s binding energies indicates that coordination bonds are presumably formed between nitrogen atom of pyridyl ligand and Ru 3+ ion in Ru-PVP/CNT.…”
Section: Pvp/cnt and Ru-pvp/cntmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Karimi and coworkers employed a magnetically separable catalyst (Fe 3 O 4 @SiO 2 -TEMPO) for the selective oxidation of HMF to DFF under metal-and halogen-free conditions. [19] In addition to organic catalysis, a series of transition-metal catalysts, such as vanadium, [20][21][22][23] manganese, [24,25] cobalt, [26] ruthenium, [27][28][29][30] copper, [31] iron, [32] silver, [33] and palladium, [34] were recently developed for HMF-to-DFF transformation and HMF conversion into 2,5-furandicarboxylic acid (FDCA) with molecular oxygen or air as the oxidants under a milder and more sustainable route.…”
Section: Introductionmentioning
confidence: 99%
“…Antonyraj et al reported total HMF conversion with 97 % DFF selectivity at 403 K under 0.28 MPa O2 after 4 h was achieved using Ru/γ-Al2O3 catalyst in toluene solvent 52) . Trimetallic mixed oxide RuCo(OH)2CeO2, which is active for aerobic oxidation of primary alcohols 53) , catalyzed HMF oxidation to DFF with 83 % yield at 97 % HMF conversion at 393 K in methyl isobutyl ketone solvent after 12 h 54 55) . The catalyst was magnetically separable and could be reused several times.…”
Section: Oxidative Transformations Of Hmfmentioning
confidence: 99%